How do business and political Networking shape overseas dispute resolution for state-owned enterprise from emerging economies. Issue 1 (February 2022) - Shen, Lu; Zhang, Chuang; Teng, Wenbo; Du, Nan
Highlights: Networking with host countries' stakeholders is a useful legitimization strategy for enterprises from emerging economies. Business and political networking affect how disputes are resolved differently for enterprises from emerging economies. The effect of networking is contingent upon firms' geographical proximity to their home central governments. Abstract: We examine how networking in host countries by state-owned multinational enterprises from emerging economies (EMNEs) influences the approaches used to resolve interfirm disputes in overseas markets. To test our hypotheses, we surveyed 127 senior Chinese executives working for overseas subsidiaries in 56 countries. The results indicate that EMNEs' business networking experience facilitates the adoption of the cooperative approach in subsequent interfirm disputes but has an insignificant effect on the competitive approach. In contrast, EMNEs' political networking experience enables them to avoid a competitive approach but has a negligible effect on the cooperative approach. Although the business networking experience of state-owned EMNEs headquartered in the capital is conducive to facilitating the cooperative approach, their political networking experience is ineffective in avoiding the competitive approach and even hinders their adoption of the cooperative approach. Overall, we highlight how networking with the key institutional actors in host countries affects EMNEs' post-entry operations.